PENDAMPINGAN LEGALITAS USAHA BAGI UMKM KULINER BEKAL SEHATKOE - Lisa Harry Sulistiowati; Noveria Susijawati; Tri Nelia (Bajang Institute, 2026)
The growing trend toward healthy lifestyles has increasingly driven demand for culinary products that are hygienic, nutritious, and practical. This condition creates opportunities for healthy culinary MSMEs to develop, including Bekal Sehatkoe, which operates in Talun District. Business legality, such as the Business Identification Number (NIB), Home Industry Food Production Permit (PIRT), and halal certification, constitute essential requirements for enhancing public trust. This community service program aims to strengthen the administrative capacity of Bekal Sehatkoe through structured and practical assistance in business legalization. The community engagement method employed is Participatory Action Research (PAR), which integrates needs identification, legal training, implementation assistance, and outcome evaluation. The results show that Bekal Sehatkoe successfully obtained an NIB as a basic operational license, gained an understanding of the stages and requirements for PIRT, and subsequently acquired halal certification. The impact of this assistance is reflected in the partner's increased readiness to develop the business professionally and to ensure long-term business sustainability.